Motherâ€™s Coping strategies toward Food Insecurity during COVID-19 Pandemic: A Review Article - Sherly Ardi Vantono; Luh Ade Ari Wiradnyani; Saptawati Bardosono (World Nutrition Journal, 2022)
The COVID-19 pandemic has impacted many aspects of the country, including the economy and health care. Food insecurity is increasing, causing harm to childrenâ€™s nutrition and development. As a result, mother must deal with food insecurity to providing a balanced diet for her children aged 6 to 23 months. This study aims to review the possible motherâ€™s coping strategies used toward food insecurity to maintain child nutrition during the COVID-19 pandemic. To review the literature, the researcher utilized search engine such as PubMed, ScienceDirect, Oxford journal, and British Medical Journal. "COVID-19", "Coping Strategies", â€œFood Securityâ€, and "Childâ€ were among the keywords chosen by the researcher. After filtering with the several criteria, the 17 articles were reviewed. Based on this paper review, we know that during the COVID19 pandemic, there is a coping strategy that assist mother to maintain their child nutrition. To address the problem of food insecurity, the possible motherâ€™s coping strategy used are adaptive coping strategies such as home-cooked meals, financial support, and receiving food assistance.